In vivo antileishmanial activity and chemical profile of polar extract from Selaginella sellowii - Dayane Priscilla de Souza Queiroz; Carlos Alexandre Carollo; Mônica Cristina Toffoli Kadri; Yasmin Silva Rizk; Vanessa Carneiro Pereira de Araujo; Paulo Eduardo de Oliveira Monteiro; Patrik Oening Rodrigues; Elisa Teruya Oshiro; Maria de Fátima Cepa Matos; Carla Cardozo Pinto de Arruda (Memorias do Instituto Oswaldo Cruz, 2016)
The polar hydroethanolic extract from Selaginella sellowii(SSPHE) has been previously proven active on intracellular amastigotes (in vitro test) and now was tested on hamsters infected with Leishmania (Leishmania) amazonensis (in vivo test). SSPHE suppressed a 100% of the parasite load in the infection site and draining lymph nodes at an intralesional dose of 50 mg/kg/day × 5, which was similar to the results observed in hamsters treated with N-methylglucamine antimonate (Sb) (28 mg/Kg/day × 5). When orally administered, SSPHE (50 mg/kg/day × 20) suppressed 99.2% of the parasite load in infected footpads, while Sb suppressed 98.5%. SSPHE also enhanced the release of nitric oxide through the intralesional route in comparison to Sb. The chemical fingerprint of SSPHE by high-performance liquid chromatography with diode-array detection and tandem mass spectrometry showed the presence of biflavonoids and high molecular weight phenylpropanoid glycosides. These compounds may have a synergistic action in vivo. Histopathological study revealed that the intralesional treatment with SSPHE induced an intense inflammatory infiltrate, composed mainly of mononuclear cells. The present findings reinforce the potential of this natural product as a source of future drug candidates for American cutaneous leishmaniasis.